'Putting the GREAT Back into Britain': National Identity, Public‐Private Collaboration & Transfers of Brand Equity in 2012's Global Promotional Campaign. (27th March 2014) - Pamment, James
Research Highlights and Abstract This article provides A 'zeitgeist' analysis of how the Coalition leadership tried to make the most of Britain's 'big year' of 2012, particularly in terms of the government's 'prosperity agenda'; Rich empirical data about high profile, government‐wide trends in British promotional strategies and practices in the context of austerity; Analysis of the consequences of these promotional activities from a number of perspectives, including: GREAT as an alternative to existing promotional structures; strategies for drawing upon national identity in support of economic growth; disciplining techniques for enforcing brand identity; approaches to co‐branding corporate and governmental Britain; the metrics used to demonstrate impact. The GREAT campaign is one of the most ambitious national promotion efforts ever undertaken. Timed to make the most of Britain's raised profile during Olympic year, the aim was to promote trade, investment and tourism under a unified identity emphasising British achievements. However, the campaign raises a number of issues. The first is how and why GREAT emerged as an alternative to established structures for soft power, public diplomacy and marketing in the UK. The second is the ways GREAT engages with collective identity through the nationalisation and commodification of symbolic resources. Third is the practices used to include and exclude specific target groups and stakeholders. Fourth is the interaction between economic and symbolic resources, including public‐private collaboration and the evidence used to determine impact and value. These themes contribute to an analysis of GREAT that will be of interest to scholars of politics and IR in the UK and internationally.